Critical Synthesis Package: Matched Pair Instrument (MPI) in Doctor-Patient Communication Skills - Hugh Stoddard (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health sciences education for the Matched Pair Instrument (MPI) in Doctor-Patient Communication Skills; (2) a copy of the MPI in Doctor-Patient Communication Skills developed by Jocelyn Lockyer, PhD. The MPI in Doctor-Patient Communication Skills is a questionnaire tool that is administered simultaneously to both the doctor and the patient following a single clinical encounter in the outpatient setting. The instrument measures the communication skills of the physician simultaneously from the perspective of both the patient and the physician. It was shown to have construct validity for use with practicing physicians; however, its validity is sensitive to both the medical context and social context in which it is used. The instrument was not designed as an educational tool and it does not have a scoring guide or performance standards that would be necessary in order to use it for educational assessment. The MPI has not been analyzed as an educational tool and it has several known limitations to its validity and reliability, although it has acceptable reliability when a large number of responses are available. The use of the MPI for instruction or educational assessment is not supported by evidence and therefore is not recommended.